Première triennale de sculpture = eerste triënnale voor de beeldhouwkunst 17.9.1982-17.10.1982. - ATELIER 340 (Brussel : Atelier, 1982)
Anciaux, Emmanuel ; Avignon, Magdeleine ; Bastianelli, Ariane ; Baudart, Johan ; Bernard, André ; Bossuyt, Werner ; Bozzato, Georges ; Cahay, Robert ; Cardon, Eric ; Coenen, Jean ; Craps, Jean-Nicolas ; Crombé, Patrick-Frederick ; Debrabandere, Lieven ; Decker, Marc ; De Clercq, Rosita ; De Kort, Jetje ; Delattre, Alain ; De Winter, Ronald ; Duriez, Irénée Jozef ; Englert, Michèle ; Frantzen, Tom ; Freson, Florence ; Gangolf, Serge ; Gross, Rainer Georg ; Halleux, Louis ; Henrotin, Marc ; Leloup, Eric ; Mafrans, Rogier ; Manoir ; Martin-Peña, Miguel ; Mathot, Jean ; Mathy, Léa ; Mouton, Jef ; Mouvet, Michel ; Parmentier, Johan ; Pintens, Roger Jr. ; Saelens, J. Kobe ; Schlüter, Rainer H. ; Scholler, Anne ; Sentjens, Lucie ; Soubry, Bart ; Sweijd, Frank ; Uytterhoeven, Emiel ; Vaernewijck, Billy ; Van den Abeele, Jacques ; Vanderhulst, Herman ; Van Hoeydonck, Patrick ; Van Imschoot, Wannes ; Van Ransbeeck, Agnès ; Van Ruysevelt, Luc ; Vastesaeger, Huibrecht ; Verhaeghe, Bernard ; Vincent ; Voeten, Emiel ; Walrave, Eddy ; Willocx, André
boek